EVALUASI KESESUAIAN LAHAN TANAMAN KAYU PUTIH KABUPATEN BURU, PROVINSI MALUKU - Sudaryono . (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2010)
Maluku province is also famous as a producer of cajeput oil in Indonesia’s number one, but its potential until now have not been optimally utilized in accordance with the carrying capacity of land for public welfare. Melaleuca Cajeputi Roxb have not managed intensively as industrial plants, consequently low production. Based on the results of land suitability assessment, pewilayahan eucalyptus trees on the island of Buru include areas that are not so large, that is 188,743 ha or 20.60% of the total area of the island of Buru, with the details:Land is very suitable (S1) covering 54,832 hectares, or 6 percent of the total land area,mainly scattered in the northern part of Buru District, the floodplain physiography. Enough suitable land class (S2) on Buru Island reached a total area of 45,404 hectares of territory, with the main limiting factor is the rainfall and slope. Class marginal land suitable (S3) with severe limiting factor on regional conditions and slope roots reach a total area of 88,507 hectares.Class of land not available for this moment (N1) reached 513,937 hectares with a very heavy barrier so that if the current efforts will be made to harm the environment or very costly. Spread primarily on physiography tectonics with sloping hills more than 25 percent and its height more than 400 m above sea level. Land Not Available forever (N2) are lands that have very severe limiting factor, so for good both physically and economically impossible to be undertaken.Keywords: capability, suitability, land, cajuput oil